A Phase II Trial of Adjuvant Durvalumab Following Trimodality Therapy for Locally Advanced Esophageal and Gastroesophageal Junction Adenocarcinoma: A Big Ten Cancer Research Consortium Study - Mamdani, Hirva; Schneider, Bryan; Perkins, Susan M.; Burney, Heather N.; Kasi, Pashtoon Murtaza; Abushahin, Laith I.; Birdas, Thomas; Kesler, Kenneth; Watkins, Tracy M.; Badve, Sunil S.; Radovich, Milan; Jalal, Shadia I. (Frontiers in Oncology, 2021)
Background: Most patients with resectable locally advanced esophageal and gastroesophageal junction(GEJ) adenocarcinoma(AC) receive concurrent chemoradiation(CRT) followed by esophagectomy. The majority of patients do not achieve pathologic complete response(pCR) with neoadjuvant CRT and the relapse rate is high among these patients. Methods: We conducted a phase II study (ClinicalTrials.gov Identifier:NCT02639065) evaluating the efficacy and safety of PD-L1 inhibitor durvalumab in patients with locally advanced esophageal and GEJ AC who have undergone neoadjuvant CRT followed by R0 resection with evidence of persistent residual disease in the surgical specimen. Patients received durvalumab 1500 mg IV every four weeks for up to one year. The primary endpoint was 1-year relapse free survival(RFS). Secondary endpoint was safety and tolerability of durvalumab following trimodality therapy. Exploratory endpoints included correlation of RFS with PD-L1 expression, HER-2 expression, and tumor immune cell population. Results: Thirty-seven patients were enrolled. The majority(64.9%) had pathologically positive lymph nodes. The most common treatment related adverse events were fatigue(27%), diarrhea(18.9%), arthralgia(16.2%), nausea(16.2%), pruritus(16.2%), cough(10.8%), and increase in AST/ALT/bilirubin(10.8%). Three(8.1%) patients developed grade 3 immune mediated adverse events. One-year RFS was 73% (95% CI, 56%-84%) with median RFS of 21 months (95% CI, 14-40.4 months). Patients with GEJ AC had a trend toward superior 1-year RFS compared to those with esophageal AC (83% vs 63%, p = 0.1534). There was a numerical trend toward superior 1-year RFS among patients with PD-L1 positive disease compared to those with PD-L1 negative disease, using CPS of ≥10 (100% vs 66.7%, p=0.1551) and ≥1 (84.2% vs 61.1%, p=0.1510) cutoffs. A higher relative proportion of M2 macrophages and CD4 memory activated T cells was associated with improved RFS (HR=0.16; 95% CI, 0.05-0.59; p=0.0053; and HR=0.37; 95% CI, 0.15-0.93, p=0.0351, respectively). Conclusion: Adjuvant durvalumab in patients with residual disease in the surgical specimen following trimodality therapy for locally advanced esophageal and GEJ AC led to clinically meaningful improvement in 1-year RFS compared to historical control rate. Higher PD-L1 expression may have a correlation with the efficacy of durvalumab in this setting. Higher proportion of M2 macrophages and CD4 memory activated T cells was associated with superior RFS.